Integrasi Teori Difusi Inovasi dan Perilaku Berencana untuk Memprediksi Perilaku Adopsi Sistem Tanam Jajar Legowo - Putra, Rizki Aditya; Oktaviyani, Rena; Amanah, Siti; Sadono, Dwi; Fatchiya, Anna (Universitas Galuh, 2025)
Jajar legowo is a rice planting technique that has been proven to increase rice productivity, but its adoption among farmers is still low. The diffusion of innovation theory and the theory of planned behavior are considered instrumental in explaining the behavior of innovation adoption. The purpose of this research is to analyze the phenomenon of farmers' innovation adoption behavior in the field by integrating these two theories. The research methodology employed is a qualitative approach through a literature review from reputable sources and interviews with farmers. The results of this study indicate that the integration of the Diffusion of Innovation and Theory of Planned Behavior provides deeper insights into the behavior of agricultural innovation adoption. Farmers' adoption behavior is influenced by innovation characteristics and subjective norms supported by external forces and self-efficacy. Farmers' perceptions of the Jajar Legowo system, which increases yields and reduces production costs, have a strong influence on their adoption intentions. Social norms, especially the influence of extension workers and farmer groups, play a significant role in shaping adoption intentions. Additionally, perceived behavioral control and farmers' self-efficacy in implementing this system are key determinants in successful adoption.